2014
DOI: 10.1155/2014/610273
|View full text |Cite
|
Sign up to set email alerts
|

Preablation Stimulated Thyroglobulin/TSH Ratio as a Predictor of Successful I131Remnant Ablation in Patients with Differentiated Thyroid Cancer following Total Thyroidectomy

Abstract: Background. About 90% of thyroid cancers are differentiated thyroid cancers. Standard treatment is total thyroidectomy followed by radioactive I131remnant ablation and TSH suppression with thyroxine. Unsuccessful ablation drastically affects the prognosis of patients with DTC particularly high risk individuals; therefore, identifying the factors that affect the success of ablation is important in the management of patients with DTC. sTg is a good predictor of successful ablation in DTC. Its levels can be influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 28 publications
1
11
1
Order By: Relevance
“…Our study was performed on a large number of patients with nonmetastatic DTC, and demonstrated that the Tg/TSH ratio is significantly more associated with ablation outcome than Tg alone. This finding is consistent with a previous study by Zubair Hussain et al Results of several noncontrolled retrospective studies suggest that a TSH value of >30 mU/L is associated with increased I‐131 uptake in tumors . In contrast, studies using single‐dose exogenous TSH stimulation suggest that maximal thyrocyte stimulation is reached when TSH levels are between 51 and 82 mU/L …”
Section: Discussionsupporting
confidence: 92%
“…Our study was performed on a large number of patients with nonmetastatic DTC, and demonstrated that the Tg/TSH ratio is significantly more associated with ablation outcome than Tg alone. This finding is consistent with a previous study by Zubair Hussain et al Results of several noncontrolled retrospective studies suggest that a TSH value of >30 mU/L is associated with increased I‐131 uptake in tumors . In contrast, studies using single‐dose exogenous TSH stimulation suggest that maximal thyrocyte stimulation is reached when TSH levels are between 51 and 82 mU/L …”
Section: Discussionsupporting
confidence: 92%
“…Many studies report that high sTg level before the first 131 I ablation is associated with lower success rate of 131 I ablation and sTg has an important predictive value for successful 131 I ablation (13, 34–36). Tamilia et al (37) and Zubair et al (38) report that the cutoff sTg values for prediction of successful or unsuccessful thyroid remnant ablation are 6 and 18 ng/ml, respectively. In these two studies, the sensitivities of sTg to predict unsuccessful thyroid remnant ablation are 67 and 76.7%, respectively, and the specificities are 79 and 79.1%, respectively (37, 38).…”
Section: Discussionmentioning
confidence: 99%
“…Tamilia et al (37) and Zubair et al (38) report that the cutoff sTg values for prediction of successful or unsuccessful thyroid remnant ablation are 6 and 18 ng/ml, respectively. In these two studies, the sensitivities of sTg to predict unsuccessful thyroid remnant ablation are 67 and 76.7%, respectively, and the specificities are 79 and 79.1%, respectively (37, 38). Our data also display that the success rate of the first 131 I ablation is clearly lower in the group with higher pre-ablation sTg level.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, some studies have reported that the serum Tg/serum TSH ratio was an important predictor of ablation success that correlated well with patient outcomes. Moreover, they suggested that this rate and similar laboratory parameters might be considered while determining risk stratifications of DTC patients (13,14). Although a high TSH level (≥30 mIU /L) is recommended for ablation success in all textbooks, to the best of our knowledge there is only one study that assesses the correlation between ablation success and low TSH level (<30 mIU/L) in the literature.…”
Section: Discussionmentioning
confidence: 99%